(untitled) (CIPEEX, 2022)
The present research seeks to analyze education and its contributions to the city of Ceres-GO in light of the Protestant ethos evidenced in the praxis of the Evangelical Educational Association (AEE) from 1947 to 2017. The objective of the research is to address the following issue: how did the pioneers who participated in the birth of the National Agricultural Colony of Goiás (CANG), and subsequently the city of Ceres, contribute to the development of education in the region, based on the Protestant ethos, through the AEE, despite the challenges of the new reality with its lack of road, school, medical, and social infrastructure as a whole? The methodology is based on Weberian sociology of meanings and history (WEBER, 2001). It involves qualitative-quantitative research conducted through documents such as books, letters, minutes, theses, and interviews with people who experienced this history. As a result of the present research, the aim is to collect documents and store them at CEDOCH/UniEvangelica/AEE for future research; it is expected to deepen the historical debate on this topic through a scientific perspective; to reinforce the contributions of the Protestant ethos in the formation of what is today the city of Ceres, based on parallels with what has occurred in various places around the world, and to motivate people towards a rational action based on values for the transformation and sustainable development of society. As a partial conclusion, the influence of AEE in the city of Ceres and the Vale de São Patrício is verified, offering an education aimed at the formation of agents of social transformation based on a system that takes into account the awareness directed towards sustainable development.